9514 1404 393
Answer:
(36°, 67°, 77°)
Explanation:
The problem statement lets us write the equations ...
x + y + z = 180 . . . . sum of angles in a triangle
y + z = 4x . . . . . 2nd and 3rd total 4 times the first
z = y +10 . . . . . . 3rd is 10 more than 2nd
__
Substituting for z in the second equation, we have ...
y +(y +10) = 4x
y +5 = 2x . . . . . . divide by 2
y = 2x -5 . . . . . . rearranged
z = 2x +5 . . . . . . substitute for y in the last equation
Now, we can write the first equation entirely in terms of x:
x +(2x -5) +(2x +5) = 180
5x = 180
x = 36
y = 2(36) -5 = 67
z = 67 +10 = 77
The three angles are (x, y, z) = (36°, 67°, 77°).